TİPİK BETONARME BİR YAPININ FARKLI ZEMİN PROFİLLERİ VE DEPREM YÜKLERİ ALTINDA YAPI-ZEMİN ETKİLEŞİMİNİN SONLU ELEMANLAR YÖNTEMİYLE ANALİZİ - ÖZBEY, İMRAN (Fırat Üniveristesi, 2024)
Türkiye, sahip olduğu faylar sebebiyle deprem tehlikesi yüksek bölgeler barındırmaktadır. Bu faylarda olan depremler geçmişten günümüze kadar birçok can alıp, yüzbinlerce yapının hasarına sebep olmuştur. Depremin sebebiyet verebileceği hasarların en aza indirilebilmesi için hesap aşamasında her detay düşünülerek tasarım yapılmalıdır. Yapı-zemin etkileşiminin deprem esnasında yapının davranışına doğrudan etki edeceği ve özellikle zemin şartlarının yetersiz olduğu durumlarda hesaba katılmasının gerektiği yapılan çalışmalar ile anlaşılmıştır. Bu çalışmanın amacı yapı-zemin etkileşiminin yapı ve zemin davranışları üzerinde etkisinin doğru bir şekilde incelenmesini sağlamaktır. Bu amaç kapsamında, Elazığ ilinde farklı zemin özelliklerine sahip dört ayrı noktada inşa edilecek bodrum + zemin + 9 normal kata sahip tipik bir betonarme yapının, üç farklı sismik kuvvete ve tasarım spektrumlarına maruz kalması durumunda yapı-zemin etkileşimi analiz edilmiştir. Her durum sonlu elamanlar yöntemi prensibi ile çalışan Plaxis 3D ve SAP2000 programları ile TBDY 2018 esaslarına göre ayrı ayrı analiz edilmiş. Ayrıca yapı-zemin etkileşiminin ihmal edildiği durumlar için de analizler gerçekleştirilmiştir. Elde edilen analiz sonuçları programların da mukayesesi ile karşılaştırılmıştır. Bu çalışma sonucunda, yapı-zemin etkileşiminin zemin özelliklerine bağlı olarak yapı ve zemin davranışının yanı sıra statik ve geoteknik tasarım parametrelerini de önemli ölçüde değiştirdiği anlaşılmıştır.

Turkey has regions with high earthquake hazard due to its faults. Earthquakes along these faults have claimed numerous lives and caused extensive damage to hundreds of thousands of structures from the past to the present. To minimize the damage caused by an earthquake, design should be made by considering every detail in the calculation phase. Studies have shown that soil-structure interaction (SSI) directly influences the behavior of the structure during an earthquake, and it should be considered, especially in cases that ground conditions are inadequate. Aim of this study is accurately analyze the effect of SSI on structure and soil behavior. For this purpose, the soil-structure interaction of a typical reinforced concrete building with a basement, a ground floor, and nine additional floors to be constructed at four different locations with varying soil properties in Elazığ is analyzed. This analysis is conducted to assess the structure's response to three different seismic forces and design spectrums. Each case was analyzed separately with Plaxis 3D and SAP2000 programs, both of which operate on the finite element method in accordance with the Turkish Building Earthquake Code (TBEC-2018) principles. Analyses were also performed for cases where SSI was neglected. The results of these analyses were then compared to evaluate the performance of the programs. The study's findings underscored that soil-structure interaction (SSI) has a substantial impact on the behavior of structures and soil, influencing various static and geotechnical design parameters, particularly in response to soil properties.
Analysis of soil-structure interaction of a typical reinforced concrete building under different soil profiles and earthquake loads by finite element method
Keywords: İnşaat Mühendisliği